A Research on Organizational Capability and Their Strategic Impact on Manufacturing Industry - Dev, Sandeep Singh; Gill, Ankur; Singh, Supinderjit (Asian Review of Mechanical Engineering, 2018)
Organizational capabilities can be viewed as the organizational context in which the organization members work in order to contribute to growth, service or other organizational goals. The research seeks to achieve in-depth understanding of impact of various organization capabilities on firm performance. Quantitative survey method was adopted for research and data was collected from 41 small and medium scale manufacturing organizations of Punjab. This paper explores how R&D capabilities, human resource capabilities, process innovation capabilities, product innovation capabilities and manufacturing capabilities influence the performance of organizations. Descriptive analysis has been derived from the study, followed by regression analysis, pearson correlation analysis, cronbach alpha and analytical hierarchy process (AHP). The findings suggest that there is significant and positive relationship between organization capabilities and firm performance. Firm performance is measure of two variables namely sales performance and financial performance. The results reveal that R&D capabilities and process innovation capabilities play vital role in achieving better sales performance whereas better financial performance can be achieved from process innovation capabilities and product innovation capabilities.